Pendayagunaan Dana Zakat Pada Lembaga Program Zakat Community Development Badan Amil Zakat Nasional Di Desa Cemplang Kecamatan Cibungbulang Kabupaten Bogor - Sobarna, Nanang; Al Murtadho, Adzka Muhammad Azzam; Sandjaya, Teguh (Jurnal Inspirasi, 2022)
This study aims to conduct an in-depth study related to the utilization of zakat funds in the Zakat Community Development program institution of the National Amil Zakat Agency (ZCD BAZNAS) in the context of empowering the mustahik economic dimension carried out in Cemplang village, Bogor Regency. This research is a type of qualitative research through a descriptive approach. The data collection technique used is using data collection techniques with document documentation used are documents or catalog records and information from official social media ZCD BAZNAS related to program institutions in Cemplang village. Based on the results of the study, it was found that the productive zakat fund utilization program provided by the BAZNAS ZCD program institution became a solution in overcoming the problem of economic inequality in the community where this program helped mustahik in improving and increasing their economic income. This utilization program has been given to mustahik in Cemplang village in 2 (two) farmer groups, namely POKTAN Berkah (Blessing Farmers Group) which runs a type of business in the field of banana cultivation, and POKDAKAN Tunas Karya (Tunas Karya Fish Farmer Group) which runs a type of business in the fish sector. Penelitian ini bertujuan untuk melakukan telaah mendalam terkait pendayagunaan dana zakat pada lembaga program Zakat Community Development Badan Amil Zakat Nasional (ZCD BAZNAS) dalam rangka pemberdayaan pada dimensi ekonomi mustahik yang dilakukan di desa Cemplang Kabupaten Bogor. Penelitian ini adalah jenis penelitian kualitatif melalui pendekatan deskriptif. Teknik pengumpulan data yang digunakan adalah menggunakan teknik pengumpulan data dengan dokumentasi dokumen yang digunakan adalah dokumen atau catatan katalog dan informasi dari sosial media resmi ZCD BAZNAS yang berhubungan dengan lembaga program yang berada di desa Cemplang. Berdasarkan hasil penelitian ditemukan bahwa Program pendayagunaan dana zakat produktif yang diberikan oleh lembaga program ZCD BAZNAS menjadi suatu solusi dalam mengatasi permasalahan kesenjangan ekonomi masyarakat dimana program ini membantu mustahik dalam memperbaiki dan meningkatkan pendapatan ekonomi mereka. Program pendayagunaan ini telah diberikan kepada mustahik di desa Cemplang dalam 2 (dua) kelompok tani yaitu POKTAN Berkah (Kelompok Tani Berkah) yang menjalankan jenis usaha dibidang budidaya pisang, dan POKDAKAN Tunas Karya (Kelompok Tani Ikan Tunas Karya) yang menjalankan jenis usaha dibidang ikan nila.